2009
DOI: 10.1007/s12355-009-0068-7
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing sugarcane yield through efficient planting methods and nutrient management practices

Abstract: Field experiment were conducted in Ariyalur District, Tamil Nadu, India to study the effect of plant geometry, planting method, along with intercropping and nutrient management practices in sugarcane var. Co 86032. The experiment was conducted in spilt plot design and replicated thrice. The main plot consists of eight treatments of different spacing, setts placement, intercropping and their combinations. The sub plot treatments consist of four different nutrient management practices namely, recommended dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…This finding is in conformity with the findings of Guru (1997). Similar findings of increased number of millable canes due to green manuring were also reported by Jayapaulet al (2000), Udayakumar (2003), Roodagi (2001), Manimaran et al(2009) and Ombase et al (2018). Among the sixteen treatment combinations, planting sugarcane at 150 cm in double rows and intercropping with sunnhemp (M2S4) produced the highest number of millable canes (110.90×10 3 and 93.13×10 3 ha -1 during 2016-17 and 2017-18, respectively).…”
Section: Number Of Millable Canesupporting
confidence: 83%
“…This finding is in conformity with the findings of Guru (1997). Similar findings of increased number of millable canes due to green manuring were also reported by Jayapaulet al (2000), Udayakumar (2003), Roodagi (2001), Manimaran et al(2009) and Ombase et al (2018). Among the sixteen treatment combinations, planting sugarcane at 150 cm in double rows and intercropping with sunnhemp (M2S4) produced the highest number of millable canes (110.90×10 3 and 93.13×10 3 ha -1 during 2016-17 and 2017-18, respectively).…”
Section: Number Of Millable Canesupporting
confidence: 83%
“…Experiments conducted at Kolhapir, Maharashtra (Saini et al 2006) indicated that pressmud cake @ 10 t ha -1 for plant crop and trash mulch @ 5 t ha -1 for the ratoon crop in conjunction with recommended NPK sustained 13-16 t ha -1 more cane yield. Wider row spacing of 120 cm row spacing with cross planting, intercropping blackgram followed by sunnhemp and application of recommended dose of fertilizers along with Acetobacter (@ 10 kg ha -1 ) and foliar spraying of micronutrient mixture (1% at 45 and 75 DAP) recorded the highest single cane yield of 150 t ha -1 (Manimaran et al 2009). The highest number of millable canes and cane length were recorded with sulphitation pressmud @ 10 t ha -1 ?…”
Section: Integration Of Organics Chemical Fertilizers and Biofertilimentioning
confidence: 99%
“…Penggunaan benih ganda dalam tata tanam juring ganda menyebabkan peningkatan populasi tanaman (Ehsanullah et al, 2011). Populasi tanaman tinggi tidak mengganggu pertumbuhan batang tebu bila kebutuhan energi cahaya dan ketersediaan nutrisi dalam tanah terpenuhi (Manimaran et al, 2009). Tata tanam juring ganda dengan dosis pupuk dua kali dosis tata tanam juring tunggal mampu meningkatkan energi cahaya tersedia 9.7-15.1% dan ketersediaan nutrisi dalam tanah (Djumali et al, 2016).…”
Section: Penampilan Tebu Yang Berasal Dari Benih Bagal Pada Dua Tata unclassified